Improving Sleep Quality Through Lavender Aromatherapy in Patients Admitted to The Intensive Care Unit - Ai Rodiah; Indah Kurniawati; Farahul Jannah (Jurnal Kesehatan Budi Luhur: Jurnal Ilmu-Ilmu Kesehatan Masyarakat, Keperawatan, dan Kebidanan, 2025)
Sleep is a fundamental human need, and a vital aspect that requires special attention in ICU patients, as proper sleep contributes significantly to the recovery process. Various pharmacological and non-pharmacological therapies have been developed to help improve human sleep quality, one of which is the use of lavender aromatherapy. This study aims to analyze the effect of lavender aromatherapy on improving sleep quality in patients admitted to the ICU. This is a pre-experimental study with a one-group pre-test and post-test design. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI). Lavender aromatherapy was administered using a diffuser. The total population in this study were 91 ICU patiens and sample involved 40 ICU patients from RSPAD Gatot Soebroto. Sample size using Lemeshow formula for estimating the proportion of a population. Data were analyzed with paired T-test. The results showed that the average sleep quality before the intervention was 5.6 with poor sleep quality, and after intervention the average was 4.1 with good sleep quality. This research of the hypothesis test showed a significant improvement in sleep quality (p-value = 0.000). It can be concluded that lavender aromatherapy is effective in improving the sleep quality of patients.